Mixed-dimensional poromechanical models of fractured porous media - Boon, W. M.; Nordbotten, J. M. (Acta mechanica, 2023)
We combine classical continuum mechanics with the recently developed calculus for mixed-dimensional problems to obtain governing equations for flow in, and deformation of, fractured materials. We present models in both the context of finite and infinitesimal strain, and discuss nonlinear (and non-differentiable) constitutive laws such as friction models and contact mechanics in the fracture. Using the theory of well-posedness for evolutionary equations with maximal monotone operators, we show well-posedness of the model in the case of infinitesimal strain and under certain assumptions on the model parameters.